First records of sponge-dwelling shrimp Synalpheus coutierei Banner, 1953 (Crustacea: Decapoda) from the west coast of India - Barkha Purohit; Kauresh D. Vachhrajani (Journal of Fisheries, 2020)
The occurrence of the two pairs of mature sponge dwelling shrimp Synalpheus coutierei Banner, 1953 is reported first time from the west coast in Gujarat, India. This species is previously reported from the east coast of India. The detailed morphological characteristic and distribution of the species are given in the paper.